Do Military Personnel "Acquire" the Capability for Suicide From Combat? A Test of the Interpersonal-Psychological Theory of Suicide. (May 2016) - Bryan, Craig J.; Sinclair, Sungchoon; Heron, Elizabeth A.
The interpersonal-psychological theory of suicide has been the focus of considerable empirical investigation over the past decade. However, little research has focused on the theory's proposition that the capability for suicide is "acquired" as a consequence of exposure to painful and provocative experiences such as violence, aggression, and trauma. To determine if capability for suicide is "acquired" over time, we conducted a prospective study of 168 military personnel deployed to Iraq. Capability scores remained stable over the course of 2 years from pre- to postdeployment, even among military personnel reporting high combat exposure. Significant positive correlations among capability and combat exposure were comparable both before and after deployment. These findings suggest that capability for suicide was not "acquired" following combat exposure in this sample of military personnel. Capability was, instead, a stable construct.